Metastatic Triple Negative Breast Cancer: The New Era of Thinking - Mohammed Amrallah A.; Elbassuiony Mohamed A.; Rashied Hanaa (Forum of Clinical Oncology)
The heterogeneity of triple negative breast cancer (TNBC) is reflected in a bizarre response to therapy. Although it is chemotherapy sensitive, the failure is the usual pathway either in local or distance status. With progression in Gene Expression Profile (GEP) and other molecular techniques, TNBC is divided into sub-types with unique pathways. In the current review, we are trying to highlight based on the molecular classification of TNBC and the management based on every type.